KAJIAN POTENSI PEMANFAATAN BIOMASSA LIMBAH PERTANIAN UNTUK MEWUJUDKAN EKONOMI BERKELANJUTAN - Dwi Apriyanti Kumalasari; Khusniyah Khusniyah; Zeni Zainal Muis (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The purpose of this research is to find out the extent of the application of Sustainable Economic Innovation through the Utilization of Agricultural Waste as Renewable Energy. This research method is qualitative with descriptive analysis All data used in this study are sourced from books, encyclopedias, journals, magazines, newspapers, and other literature materials because it is a literature review. The results of this study are that the potential of agricultural waste in Indonesia as a source of renewable energy is really extraordinary. With the right technology management, policy support, and stakeholder synergy, this potential can be transformed into clean energy, reduce emissions, strengthen the village economy, and increase national energy security.